2022
DOI: 10.3390/systems10040097
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Balancing Effect of a Digital Green Innovation (DGI) Network to Improve the Performance of DGI for Industry 5.0: Roles of Digital Empowerment and Green Organization Flexibility

Abstract: Under the background of double carbon target and digital intelligence era, the innovation resources and innovation environment that manufacturing enterprises rely on have shown exponential growth. Digital green innovation (DGI) has gradually become the mainstream paradigm of innovation. How to achieve a balance between a local DGI network (LDGIN) and a remote DGI network (RDGIN) and how to use the role of digital empowerment and green organization flexibility to improve the performance of DGI are very importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…However, economic development is usually accompanied by an increase in energy consumption, in particular, the use of fossil fuels, such as coal, oil, and natural gas. The widespread use of these fossil fuels in energy production, transportation, and industrial production has led to an increase in carbon dioxide emissions 16 . As the economy continues to develop, people are beginning to realize the impact of carbon emissions on the environment and climate.…”
Section: The Influence Mechanism Of Common Prosperity On Carbon Emiss...mentioning
confidence: 99%
“…However, economic development is usually accompanied by an increase in energy consumption, in particular, the use of fossil fuels, such as coal, oil, and natural gas. The widespread use of these fossil fuels in energy production, transportation, and industrial production has led to an increase in carbon dioxide emissions 16 . As the economy continues to develop, people are beginning to realize the impact of carbon emissions on the environment and climate.…”
Section: The Influence Mechanism Of Common Prosperity On Carbon Emiss...mentioning
confidence: 99%
“…The concept of clusters mainly comes from economic literature [31] especially related to spatial geography. The concept of social networks mainly comes from sociological literature [32]. The clusters emphasized the returns to scale within a region [33].…”
Section: Inter-firm Social Networkmentioning
confidence: 99%
“…The study demonstrated that energy efficiency policies have a significant positive effect in promoting EEM adoption [36]. Hu et al (2022) found that the balance between local DGI network (LDGIN) and remote DGI network will have an impact on the DGI performance of manufacturing enterprises [37]. He and Su (2022) found that regulatory pressure and international opportunities would magnify the impact of digital transformation on enterprises' GI [38].…”
Section: Factors Related To Dgi Performancementioning
confidence: 99%